Islamic Forum

# Algebra

## Recommended Posts

Asalaam Alaikum

What is

1./ X................4

______ = _______

2X + 1 ...........3

2./ a..................2

_______ + ______

2+a...............a+2

3./ 1..................3

_____ - ___________

x-2.........'X^2' - X - 2

Ignore the Dots, its coz i cannot do spaces

And please do du'aa that i pass the test i do

Edited by crystal_sword

##### Share on other sites

selam,

what did you write is not understandable.....you may write w/ your words???

##### Share on other sites

Assalamualikum, bro, its me from MSN, all you do is cross multiply:

1, 3X = 4(2X+1)

3X = 8X + 4

-5X = 4

x= -4/5

2, on the bottom youve got the same denominator (2+a) = (a+2), so just add the top line... = 2+a

_______ = 1

2+a

3, First factorise X^2 - X - 2

= (x+1) (x-2)

So the common denominator is (x-2)(x+1) since theres already (x-2) on the bottom of the left hand side of the sum..

Mulitiply the numerator of the left hand side by (x+1):

1(x+1) - 3

_____________________

(x+1) (x-2)

open the top line brackets:

x + 1 - 3

________

(x+1)(x-2)

the top line here is (x-2), so cancel it with the one on the bottom... =

1

____

x+1

Im assuming Q3, is just simplyfing...

hope its right :D

Edited by AbdAllah

##### Share on other sites

:D

oops got a lil late :D looks liek bro AbdALlah already solved it for you .but nonethless i'll post my solutions :P

here it goes:

1)

x/(2x+1) = 4/3 (right?)

by cross multiplication we get

3x = 4(2x+1)

=> 3x=8x+4

=> 3x-8x=4

=> -5x=4

=> x=-4/5

(thanx elif didnt note it before :P)

2)

a/(2+a) + 2/(a+2)

now (2+a) =(a+2 ) -> cumulative property wrt addition remeber??

so :

a/(2+a) + 2/(a+2) can be written as a/(a+2) + 2/(a+2)

now we see that boteh the fractions have common denomiantor

(a+2)

------- = 1 as they cancel each other!

(a+2)

3) 1/( x-2) - 3 /(x^2-x-2)

if you factorize (x^2-x-2) you get (x-2) (x+1) ! how??

coz multiplying x^2 and -2 we get -2x^2

and we know -2x+ x= -x which is equal to the middle entity

also (-2x) * (x) = -2x^2

so we can replace -x in the equation with -2x+x

now placing that in equation we get

x^2 -2x+x-2

factorizing :

x(x-2) + 1(x-2)

= (x +1) (x-2)

replacing this in teh denomintor we get

1/(x-2) - 3/(x-2)(x+1)

taking LCD

(x+1 ) - 3 (x-2)

------------- = ---------

(x+1)(x-2) (x+1)(x-2)

which is equal to 1/(x+1)

hope i simplified things?? best of luck!! :D u'll be in my prayers. you can ask if you faind anything confusing in the above solution

Edited by RAAAZ

##### Share on other sites

selam,

abdallah's solution is correct.....but there is simple mistake at number one of Raaz solution

##### Share on other sites

:D

my fault lads, I did the test without tis help, and i dont remember what i wrote :D

anyway

Whatever happens is Allah's (Swt) will

Jazakallah kair for the help brothers, it may come in handy later :P

##### Share on other sites

:D

lolz ok best of luck then!! :P you'd fare it well :P

:D

##### Share on other sites

looking at all these equations is making me go mad

i hate algabra, see i cant evan spell da damm thing

##### Share on other sites

:D

looking at all these equations is making me go mad

i hate algabra, see i cant evan spell da damm thing

See I think i'm the opposite, the more I see how easy this stuff is the more I want to teach it to the youngins :P

:D

AS